Discovery Learning Model for Enhancing Oral Activities of High School Student - WINARNI, WINARNI; SANTOSA, SLAMET; RAMLI, MURNI (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
Improving students' participation in the classroom is challenging, particularly in the oral activities. Learning strategy have to be arranged appropriately in order to provide as much as possible chance for students to do oral activities. The objective of this research is to improve oral activities of high school student by applying discovery learning model. There were 36 high school students of one public high school in Karanganyar, Indonesia purposively selected as participants. The discovery learning model was applied within 3 cycles and each cycle consists of 4 phases, namely planning, action, observation, and reflection. Data were obtained by observation, interview, and documentation, and triangulation method was conducted for validation of the data. Data were analysed based on VICS Flanders wooksheet. The result shows that student oral activities had been enhanced. The oral activities from pre-cycle to the last cycle respectively were 2.21%, 41.60%, 60.34%, and 78.75%. It can be concluded that discovery learning positively enhance student’s oral activities.